PERANCANGAN ENTERPRISE ARCHITECTURE ZACHMAN FRAMEWORK UNTUK JASA LAYANAN PASANG BARU DAN TAMBAH DAYA LISTRIK PADA PERUSAHAAN JASA LISTRIK SWASTA - Dedi Saputra (Jurnal Khatulistiwa Informatika, 2015)
Strategies and policies in a profit-oriented business venture whose mission and vision emphasis on customer service. Implementation of information systems and information technology will have an impact on the quality of service that makes the competition more competitive. The more effective and efficient utilization of IS and IT support business activities, achieve organizational goals and services for stakeholders. These objectives can be achieved optimally when the synergy between IS and IT strategy with the business strategy of the company.Build a system within a company as mentioned above require careful planning and have to pay attention to all stakeholders with the system, be it the management as the party responsible for the performance of the organization, the developer is responsible for the system is built, as well as user who is responsible for the utilization of the system being built.Efforts to avoid interference with the harmony of the system, during the development of the system, is to do the planning of the system clearly before the system is built. Planning overall system (covering all aspects of the organization) is what is known as the Enterprise Architecture (EA). One framework that addresses the problems in the construction of an information system in a company from various viewpoints is Frawework Zachman.Keywords: SI, TI, EA, Zachman Framework